Back to Nature: Exploring the Potential for Implementing the Norwegian Idea of Outdoor Days in the Slovenian School System - Gomboc, Katja (Revija za elementarno izobraževanje, 2016)
Nowadays it is common to use the expressions ‘in the classroom’ and ‘out of the classroom’ (outdoors). In this article the word ‘outdoors’ will be replaced with the words ‘in the natural environment’, ‘into the natural environment’ and ‘within the natural environment’. These words accent the equal importance of nature as a learning area, a concept that is often forgotten, neglected or ignored. In this area, Norway has forged a real connection between people and nature, a way of life called “friluftsliv,” and has used experiential learning based on learning and playing in an outdoor area. In this article is presented a research study of teaching in nature, the Norwegian nature-oriented curriculum and the implementation of nature practice in the Slovenian school system.
Keywords: nature; teaching; teaching outside the classroom; “friluftsliv”; free play